2016
DOI: 10.1183/13993003.00176-2016
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated telomere attrition in children and teenagers with α1-antitrypsin deficiency

Abstract: Numerous studies have shown that oxidative stress accelerates telomere shortening in several lung pathologies. Since oxidative stress is involved in the pathophysiology of α1-antitrypsin deficiency (AATD), we hypothesised that telomere shortening would be accelerated in AATD patients. This study aimed to assess telomere length in AATD patients and to study its association with α1-antitrypsin phenotypes.Telomere length, telomerase activity, telomerase reverse transcriptase (hTERT) expression and biomarkers of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…In line with studies showing that children suffering from chronic illnesses have shorter telomeres than healthy peers [ 10 , 11 ], we found that critically ill children have shorter leukocyte telomeres upon admission to the PICU than matched controls. In theory, this could (partly) be explained by underlying chronic diseases hallmarked by hypoxemia or inflammation, which could predispose to adverse outcomes, by previous hospital admissions or by unknown differences in environmental exposures [ 12 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with studies showing that children suffering from chronic illnesses have shorter telomeres than healthy peers [ 10 , 11 ], we found that critically ill children have shorter leukocyte telomeres upon admission to the PICU than matched controls. In theory, this could (partly) be explained by underlying chronic diseases hallmarked by hypoxemia or inflammation, which could predispose to adverse outcomes, by previous hospital admissions or by unknown differences in environmental exposures [ 12 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…This was necessary to allow adjustment for the change in neutrophil fraction from admission to last PICU day, given that neutrophils have shorter telomeres than lymphocytes [ 22 , 23 ]. This multivariable linear regression analysis of the impact of randomisation to early PN or late PN was further adjusted for (a) other determinants of telomere length, being age (as telomeres shorten with age) [ 21 ], gender (with shorter telomeres expected for boys [ 20 ]) and the telomere length upon admission, (b) the acute critical-illness -related baseline risk factors, being the admission diagnosis, the degree of organ failure (Paediatric Logistic Organ Dysfunction (PeLOD) score), the estimated risk of death (Paediatric Index of Mortality 2 (PIM2) score), the risk of malnutrition (Screening Tool for Risk on Nutritional Status and Growth (STRONGkids) risk group), whether or not there was an infection present upon admission and the treatment centre and (c) for markers of pre-existing chronic disease (height and weight as percentiles of population norms) and “chronicity” as a dichotomised label indicating whether or not the patient was suffering from any symptomatic chronic disease identified via screening of the medical history and hospital files (Additional file 1 ), with telomeres expected to be shorter in patients with chronic illnesses [ 7 , 10 , 11 , 20 , 24 ]. To also investigate whether any impact of early PN versus late PN on telomere length change over time in PICU could be mediated by its negative effect on time to recovery , the multivariable linear regression analysis of the impact of randomisation to early PN or late PN was further adjusted for the duration of PICU stay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…186 However, multiple other factors also contribute to disease severity, and much research is being done to obtain a comprehensive picture for enabling better diagnosis. [187][188][189][190][191][192][193][194][195][196] Danozol was found to significantly improve AAT circulating levels 197 without eliciting side effects. Another approach is to inhibit polymerization of AAT by small molecules, 198 peptides, 199 autophagy-enhancing drugs 200,201 (ClinicalTrials.gov:…”
Section: Asthmamentioning
confidence: 99%
“…This process can ultimately lead to disease. 4 In addition to its relationship with aging, there is ample evidence to suggest that telomeres may also play an important role during intrauterine growth and development to produce distinct pregnancy outcomes as a result of fetal programming. 5 Fetal programming is the term used to describe intrauterine mechanisms and fetal developmental trajectories that explain fetal phenotypes at birth which may be linked to adult-onset disease and disorders.…”
Section: Introductionmentioning
confidence: 99%